The American Foregut Society White Paper on the Endoscopic Classification of Esophagogastric Junction Integrity. Issue 4 (December 2022) - Nguyen, Ninh T.; Thosani, Nirav C.; Canto, Marcia Irene; Chang, Kenneth; Lipham, John; Abu Dayyeh, Barham; Wilson, Erik B.; Muthusamy, V. Raman; Clarke, John; Bell, Reginald; Janu, Peter; Swanstrom, Lee; et al.
Background: The American Foregut Society (AFS) is dedicated to advancing patient care and digestive health within the realm of foregut disease. One of the most common and debilitating esophageal conditions is gastroesophageal reflux disease (GERD). The Hill grade is an endoscopic classification of the esophagogastric junction (EGJ) based on the appearance of the gastroesophageal flap valve from a retroflexed view of the hiatus. This endoscopic classification provides insight into the anatomic disruption of the EGJ which has been shown to correlate with GERD. However, clinical utilization of this classification by endoscopists has been limited due to the perceived relevance and subjectivity of the classification. With the advent of endoscopic treatment options for GERD, there is renewed enthusiasm to develop a grading system of the EGJ that can objectively define anatomical impairment and reduce interobserver grading variability. Methods: The AFS convened a 13-member working group tasked with reviewing the Hill grade classification and formulating a proposal for its revision utilizing a modified Delphi method. This white paper summarizes the output from this working group. Results: The working group concluded that all components of the antireflux barrier—the lower esophageal sphincter and its sling fibers, the crural diaphragm, and the gastroesophageal flap valve—contribute to EGJ integrity. Using defined objective parameters of extent of hiatal axial herniation and crural disruption and presence or absence of a flap valve, the new AFS classification stratifies EGJ integrity from normal (grade 1) to increasing degrees of EGJ disruption (grade 2-4) beginning with loss of the flap valve and progressing to increasing degrees of crural disruption and hiatus hernia. This AFS classification also stipulates appropriate endoscopic methodology to utilize in making the assessment and provides a basic nomenclature for communication among endoscopists. Conclusions: The AFS endoscopic classification of the EGJ expands on the Hill classification by including assessment of axial hiatal hernia length (L), hiatal aperture diameter (D), and presence or absence of the flap valve (F) making it more comprehensive - LDF components. Future directions include validation studies correlating the ability of the AFS classification in predicting the presence and severity of GERD.